THE LEXICONS DESCRIBING PROFESSIONS USED IN ENGLISH AND UZBEK LANGUAGES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article discusses some ideas on the topic terms describing professions in two languages, English and Uzbek. Moreover, it illustrates “term” and “terminology” and origin of terminology.